The alteration history of the CY chondrites, investigated through analysis of a new member: Dhofar 1988. (15th February 2021) - Suttle, M.D.; Greshake, A.; King, A.J.; Schofield, P.F.; Tomkins, A.; Russell, S.S.
Abstract: We provide the first detailed analysis of the carbonaceous chondrite Dhofar (Dho) 1988. This meteorite find was recovered in 2011 from the Zufar desert region of Oman and initially classified as a C2 ungrouped chondrite. Dho 1988 is a monomict breccia composed of millimetre-sized clasts, between which large (∼50–250 µm) intermixed sulphide-Ca-carbonate veins formed. It has high sulphide abundances (∼14 vol%), medium-sized chondrules (avg. 530 µm, N = 33), relatively low chondrule/CAI abundances (<20 area%), a heavy bulk O-isotope composition (δ 17 O = 9.12‰, δ 18 O = 19.46‰) and an aqueously altered and then dehydrated alteration history. These characteristics are consistent with the newly defined Yamato-type (CY) carbonaceous chondrite group, suggesting this meteorite should be reclassified as a CY chondrite. Dho 1988 experienced advanced aqueous alteration [petrologic subtype 1.3 in the scheme of Howard et al. (2015)]. Alteration style and extent are similar to the CM chondrite group, with the matrix having been replaced by tochilinite-cronstedtite intergrowths and chondrules progressively pseudomorphed by phyllosilicates, sulphides and in one instance Ca-carbonates. However, departures from CM-like alteration include the replacement of chondrule cores with Al-rich, Na-saponite and upon which Cr-spinel and Mg-ilmenite grains precipitated. These late-stage aqueous alteration features are common among the CY chondrites. Fractures in Dho 1988 that are infilled by phyllosilicates, sulphides and carbonates attest to post-brecciation aqueous alteration. However, whether aqueous alteration was also active prior to brecciation remains unclear. Veins are polymineralic with a layered structure, allowing their relative chronology to be reconstructed: intermixed phyllosilicate-sulphide growth transitioned to sulphide-carbonate deposition. We estimate temperatures during aqueous alteration to have been between 110 °C < T < 160 °C, based on the co-formation of Na-saponite and tochilinite. Dho 1988 was later overprinted by thermal metamorphism. Peak temperatures are estimated between 700 °C and 770 °C, based on the thermal decomposition of phyllosilicates (both serpentine and saponite) combined with the survival of calcite. As temperatures rose during metamorphism the thermal decomposition of pyrrhotite produced troilite. Sulphur gas was liberated in this reaction and flowed through the chondrite reacting with magnetite (previously formed during aqueous alteration) to form a second generation of troilite grains. The presence of both troilite and Ni-rich metal in Dho 1988 (and other CY chondrites) demonstrate that conditions were constrained at the iron-troilite buffer.